Development of Earthquake Disaster Mitigation Learning Program for Early Childhood - Tita Sapriyanti (Universitas Negeri Padang, 2020)
The danger of earthquakes spread almost all areas of the Indonesian islands, one of them in the city of Padang, West Sumatra either on a small scale to large scale damage. The earthquake was felt not only by adults, but young children are also feeling the impact of the earthquake. So far, efforts to increase the ability of earthquake disaster preparedness much focused on adults, while for young children is still very minimal, it is necessary to provide knowledge of earthquake preparedness in children from an early age. This research is the development by using the 4D model that aims to produce learning programs earthquake disaster mitigation valid, practical, and effective. The data analysis technique used is descriptive qualitative analysis. The conclusion of the development is a learning program earthquake disaster mitigation was very valid and practical use in learning. From the results of studying the implementation of learning programs earthquake disaster mitigation, it was concluded that the child's knowledge and skills regarding earthquake preparedness increases. Thus, learning programs earthquake disaster mitigation is very effective for use in improving the preparedness of children to the earthquake.Keywords: Learning Program, Disaster Mitigation, Earthquake, Early Childhood